Effects of milling time and calcination condition on phase formation and particle size of lead zirconate nanopowders prepared by vibro-milling - O. Khamman (2018)
Effect of calcination conditions on phase formation and particle size of lead zirconate (PbZrO3) powders synthesized by a solid-state reaction with different vibro-milling times was investigated. A combination of the milling time and calcination conditions was found to have a pronounced effect on both the phase formation and particle size of the calcined PbZrO3powders. The calcination temperature for the formation of single-phase perovskite lead zirconate was lower when longer milling times were applied. The optimal combination of the milling time and calcination condition for the production of the smallest nanosized (∼28 nm) high purity PbZrO3powders is 35 h and 750 °C for 4 h with heating/cooling rates of 30 °C/min, respectively. © 2007 Springer Science+Business Media, LLC.